An Empirical Evaluation of Possible Explanations for the Differing Treatment of Apparently Similar Unusual Events - Cumming, John (Journal of Accounting Research, 1973)
John Cumming, An Empirical Evaluation of Possible Explanations for the Differing Treatment of Apparently Similar Unusual Events, Journal of Accounting Research, Vol. 11, Empirical Research in Accounting: Selected Studies 1973 (1973), pp. 60-95